Comparative Visual Acuity in Indonesian Myopic Students: Spectacles Versus Contact Lenses - Hanna Nurul Husna; Ana Mariam Desyana; Itmam Milataka (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Myopia, a leading cause of correctable visual impairment worldwide, is primarily managed with spectacles and contact lenses. In West Java, Indonesia, refractive error affects up to 18.4% of junior high school students, with myopia accounting for 94.4% of cases. Despite the widespread use of both correction modalities, direct comparisons of their visual acuity outcomes in adolescents, particularly in developing countries, remain limited. This study compared best-corrected visual acuity (BCVA) achieved with habitual spectacles and soft contact lenses among myopic Indonesian adolescents using an aggregated subject-level analytical approach. A cross-sectional observational study was conducted at a public vocational school in Tasikmalaya, West Java. Thirty-four myopic students (33 females, 1 male; aged 16–18 years) who regularly used both spectacles and soft contact lenses were recruited through purposive sampling. Monocular visual acuity was measured with a Snellen chart at six meters under standardized indoor illumination. To avoid inter-eye correlation, monocular Snellen fractions were converted to a linear scale, averaged for each participant, and transformed into logMAR values for subject-level paired analysis using the Wilcoxon signed-rank test. Half of the participants (50.0%, n=17) demonstrated identical visual acuity with both correction modalities. Among those with discordant outcomes, significantly more participants achieved better visual acuity with soft contact lenses (35.3%, n=12) than with spectacles (8.8%, n=3). Mean logMAR values were significantly better with contact lenses than spectacles (0.10±0.12 vs. 0.15±0.13; p=0.024). Soft contact lenses provided superior distance visual acuity compared with spectacles in adolescents, showing discordant outcomes. This finding is consistent with optical theory: eliminating the vertex distance reduces retinal image minification and improves focal precision. The small subgroup performing better with spectacles may reflect individual ocular surface characteristics or tear film instability affecting contact lens performance. These findings emphasize the importance of accurate refraction, routine prescription verification, and professional contact lens fitting to optimize visual outcomes in adolescent myopic patients.